Ethnographic fieldwork : a beginner's guide - Blommaert, Jan.; Jie, Dong, 1975- (Bristol, UK. : Multilingual Matters, 2010)
This text describes ethnographic fieldwork as the gradual accumulation of knowledge about something you don't know much about to begin with, facilitated by theoretical and methodological instruments. The book provides an easy to read introduction to quite complex ideas about knowledge.
Includes bibliographical references and index.
Keywords: Ethnology -- Fieldwork